RANCANG BANGUN SISTEM PEMILAH DAN PEMANTAU SAMPAH LOGAM DAN NON LOGAM VIA SMS - Hasibuan, M. Sidik; Sherina Azzahra; Afritha Amelia (Jurnal Ilmiah Tenaga Listrik, 2021)
The Continuously increasing waste production in line with the increasing population, changing consumption patterns, and people's lifestyle has increased the number of landfills, types, and diversity of garbage characteristics. The increasing number of landfills is not accompanied by the ability of the public to process waste and the lack of information obtained by janitors to clean up garbage that has accumulated adds to the problem, so that the environment becomes increasingly dirty and smelly. Therefore, it is necessary to monitor the condition of the trash can that is full by using GPS and SMS as support if the condition of the trash can be in full condition so that it can help inform the user to quickly transport the sampat. It is processed using the Arduino Nano microcontroller as a controller component. Some of the electronic components used include IR Sensor, Inductive Proximity Sensor, Ublox Neo 6MV2 GPS, Arduino Nano, and Buzzer. In this Garbage Sorting and Monitoring System, it is obtained that the servo motor will move 900 (to the right) if the proximity inductive sensor detects metal type garbage, and the servo motor will move 1800 (to the left) if the proximity inductive sensor detects non-metallic type garbage. The buzzer will then turn on when the IR sensor detects a garbage distance of 1 cm up to 4 cm.